The Urban Sensory Ambiance of Batroun’s Old Patrimonial Souk in the Face of Overtourism - Zacca, Darine; Abi Khattar Zgheib, Paul G (Alanya Üniversitesi, 2025)
The old patrimonial souk of Batroun, in northern Lebanon, is undergoing deep change due to overtourism. Once a center for local trade and crafts, the souk has shifted since the early 2000s toward tourism and commercial entertainment. This change has disrupted its multisensory ambiance, altering how long-term residents perceive, use, and emotionally connect with space. While efforts to preserve heritage are underway, they often focus more on visual and economic appeal than on lived experience, causing tension between cultural preservation and tourist development. This study fills a gap in heritage and urban studies by using Jean-Paul Thibaud’s “commented city walks” method to explore how residents describe and sense these changes. Fieldwork shows that residents increasingly feel dislocation and solastalgia as daily social rituals and sensory familiarity fade in favor of overtourism. The research adds to the growing field of urban sensory studies by demonstrating how sensory perception can help identify cultural loss in heritage sites. It also highlights the need for participatory, sensory-based planning approaches that consider the lived experiences of local communities. By viewing sensory co-construction as a potential bridge between tourism and preservation, the study promotes more inclusive urban transformation models. By foregrounding lived and actual urban sensory experiences, this research not only contributes to the field of urban sensory studies but also aligns with the journal’s aim of examining the socio-economic effects of modern urban transformation driven by overtourism, suggesting pathways toward more inclusive and resilient futures in heritage settings.